The relationship between organisational competitive advantage and performance moderated by the age and size of firms - Ismail, 'Alimin Ismadi; Che Rose, Raduan; Abdullah, Haslinda; Uli, Jegak (Asian Academy of Management and Penerbit Universiti Sains Malaysia, 2010)
It has been argued that achieving a position of competitive advantage is a necessary precursor to a firm's significant performance. This paper will empirically examine the potential moderating variables that could affect the relationship between a firm's competitive advantage and performance, namely the firms' age and size. By examining the relative moderating effects of these variables, this paper delivers valuable information to firms, specifically with regard to strategic management directed toward performance and attaining a competitive advantage. This research was conducted among 127 manufacturers listed in the 2008 Federation of Malaysian Manufacturers Directory. A cross-sectional study was conducted using a structured questionnaire to obtain responses from the manufacturers. A two-way ANOVA shows that only the age of firms is a significant moderator in the relationship between competitive advantage and performance, and that this relationship is stronger for older firms. The size of firms does not significantly moderate the relationship between competitive advantage and performance. Despite the non-significant moderating effect of firms' size, overall, this study provides empirical support for the Resource-Based View (RBV) of Malaysian manufacturers regarding the issue of competitive advantage.